Study of Solution as Locally Asymptotic Attractivity for Nonlinear Functional Integral Equation - Dr. Shantaram N Salunkhe, (Indian Journal of Advanced Mathematics (IJAM), 2025)
In this paper we proved an existence result for local asymptotic attractivity of the solution for a nonlinear functional integral equation under certain condition which gives the existence as well as existence of the asymptotic stability of solutions. An example is providing for indicating the natural realizations of abstract theory presented in the paper.